Healthcare 4.0 : next generation processes with the latest technologies - Chanchaichujit, Janya; Tan, Albert Wee Kwan, 1962-; Meng, Fanwen; Eaimkhong, Sarayoot (Palgrave Macmillan, 2019)
This book describes how the fourth industrial revolution (i.e. Health 4.0), which is based on virtualisation and service aggregation can transform the healthcare sector with the aid of technologies such as Blockchain, AI, Big data analytics and so on. It is very relevant for healthcare professionals."--Chris Holt, Leader, Global Healthcare, Amazon Business, USA This book aims to demonstrate the benefits of implementing Industry 4.0 in healthcare services and to recommend a framework to support this implementation. Key topics in this book include: (1) Discovering emerging technologies and techniques to support Healthcare 4.0, this includes the Internet of Things (IOT), Big data analytics, Blockchain, Artificial Intelligence (AI), Optimisation and Predictive Analytics; (2) Illustrating some examples of such advanced implementation in Healthcare 4.0; (3) Recommending a development process to develop health technology start-ups and entrepreneurial activities; and (4) Discuss the transformation methodology used to redesign healthcare processes in order to overcome the challenges of implementing a Healthcare 4.0 project. Janya Chanchaichujit is an Assistant Professor in Logistics and Supply chain management in the School of Management at Walailak University in Thailand. Albert Tan is an adjunct professor in Supply Chain Management at Malaysia Institute for Supply Chain Innovation, Malaysia. Fanwen Meng is an operations research specialist at National Healthcare Group, Singapore. Sarayoot Eaimkhong is senior consultant at the Technology Management Center, National Science and Technology Development Agency (NSTDA), Thailand.- Resumé vydavatel
Keywords: lékařská technika; zdravotní péče; zdravotní služby; blockchain (technologie); umělá inteligence; sběr dat; analýza dat; medical technology; health care; health services; blockchain (technology); artificial intelligence; data collection; data analysis; elektronické knihy; kolektivní monografie; electronic books; collective monographs